Employees’ Job Satisfaction in Tertiary Level Hospitals (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: In a resource-limited and high burden disease setting, satisfied human resource is an asset in terms of high productivity, efficiency and quality care.Objective: To evaluate and analyze the employees’ job satisfaction at tertiary level hospitals and identify the important determinants for job satisfaction.Materials and Methods: This descriptive study was done in two leading specialized private owned hospitals of Bangladesh during January 2011 to April 2011. A group of 200 employees were selected from both clinical (60%) and non-clinical (40%) staffs through systematic sampling method. Self-administered structured questionnaire was used keeping focus on organizational supportive activities, management employee relationship, gender discrimination and overall job satisfaction.Results: Male and female participants were nearly equal, 75% female respondent was satisfied/highly satisfied on their job which was higher than male (55%)(P